A concise, efficient synthesis of sugar-based benzothiazoles through chemoselective intramolecular C–S coupling - Shen, Chao (2013)
Sugar-based benzothiazoles are a new class of molecules promising for many biological applications. Here, we have synthesized a wide range of sugar-based benzothiazoles from readily accessible glycosyl thioureas by chemoselective, palladium-catalyzed C–S coupling reactions. Corroborated by theoretical calculations, a mechanistic investigation indicates that the coordination to the palladium by a pivaloyl carbonyl group and the presence of intramolecular hydrogen bonding play important roles in the efficiency and chemoselectivity of reaction. These fluorescent glycoconjugates can be observed to readily enter mammalian tumor cells and exhibit potential in vitro antitumor activity.